Divergence and plasticity shape adaptive potential of the Pacific oyster. Issue 11 (November 2018) - Li, Li; Li, Ao; Song, Kai; Meng, Jie; Guo, Ximing; Li, Shiming; Li, Chunyan; De Wit, Pierre; Que, Huayong; Wu, Fucun; Wang, Wei; Qi, Haigang; et al.
Abstract The interplay between divergence and phenotypic plasticity is critical to our understanding of a species' adaptive potential under rapid climate changes. We investigated divergence and plasticity in natural populations of the Pacific oysterCrassostrea gigas with a congeneric oysterCrassostrea angulata from southern China used as an outgroup. Genome re-sequencing of 371 oysters revealed unexpected genetic divergence in a small area that coincided with phenotypic divergence in growth, physiology, heat tolerance and gene expression across environmental gradients. These findings suggest that selection and local adaptation are pervasive and, together with limited gene flow, influence population structure. Genes showing sequence differentiation between populations also diverged in transcriptional response to heat stress. Plasticity in gene expression is positively correlated with evolved divergence, indicating that plasticity is adaptive and favoured by organisms under dynamic environments. Divergence in heat tolerance—partly through acetylation-mediated energy depression—implies differentiation in adaptive potential. Trade-offs between growth and survival may play an important role in local adaptation of oysters and other marine invertebrates. Adaptive differentiation is poorly understood in marine systems. Here, the authors combine genome sequencing with gene expression and physiology to show that genetic divergence and plasticity contribute to local adaptation of Pacific oyster populations.